Integration and Inclusion of Racialized Immigrants in Canada's Expanding Environmental Sector: Toward Economic and Environmental Justice. - Patterson, Mei-Ling; Edge, Sara (Canadian Ethnic Studies, 2025)
Climate change, the transition to net-zero emissions, and environmental health challenges are contributing towards a rapidly expanding environmental sector and investment in green and clean technology products in Canada. Concomitantly, the federal government committed to unprecedented levels of immigration from 2022 to 2024 for sustained economic growth and to support labour market gaps. Despite Canada's heavy reliance on highly skilled racialized migrants, economic integration studies continue to document the deskilling of migrants upon arrival and inequities in the labour market. Scholars have also documented the disproportionate exposure to environmental hazards faced by racialized migrants compounding existing inequities and exclusion. With the rapid development of the environmental sector including the creation of thousands of new sustainable jobs, Canada has a unique opportunity to not only overcome legacies of exclusion of racialized migrants in the labour market but improve prospects for addressing widespread environmental injustices facing this population. Drawing upon focus groups, this paper examines the experiences of young highly skilled racialized immigrants integrating into Canada's environmental sector (n=15). We also draw upon key informant interviews with environmental professionals in Canada (n=14) to further understand what barriers and strategies exist for the labour market integration of racialized migrants. Our findings demonstrate barriers and opportunities for strengthening economic and environmental justice through inclusion and equitable access to Canada's environmental sector.